Internationale Jungfischuntersuchungen in der Nordsee 1980 - Wagner, G.; Wegner, Gerd (1980)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010